2001
DOI: 10.1007/bf02981995
|View full text |Cite
|
Sign up to set email alerts
|

Neutrophil Functions of Patients With Vasculitis Related to Myeloperoxidase-Specific Anti-Neutrophil Antibody

Abstract: Neutrophils are hypothesized to cause tissue damage resulting in the development of vasculitis and glomerulonephritis, although they are known to primarily take part in host defense functions. The infiltration of inflammatory cells. notably neutrophils and macrophages, is observed in the progression of vasculitis. Neutrophils with activated status and anti-neutrophil cytoplasmic antibodies (ANCAs), especially myeloperoxidase-specific (MPO)-ANCA, have been implicated in the development of vasculitis. The target… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0
1

Year Published

2003
2003
2024
2024

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 15 publications
(6 citation statements)
references
References 42 publications
0
5
0
1
Order By: Relevance
“…NET components, including MPO, which can mediate the generation of hypochlorite (OCl − ) (21), histones (22), and matrix metalloproteinases (MMP), particularly MMP-2 and MMP-9 (23), have been demonstrated as strong effectors that induced vascular endothelial cell damage. In fact, the presence of extracellular MPO and NET-related molecules, such as histones, has been shown in the glomerular lesions of AAV (10, 24, 25).…”
Section: Discussionmentioning
confidence: 99%
“…NET components, including MPO, which can mediate the generation of hypochlorite (OCl − ) (21), histones (22), and matrix metalloproteinases (MMP), particularly MMP-2 and MMP-9 (23), have been demonstrated as strong effectors that induced vascular endothelial cell damage. In fact, the presence of extracellular MPO and NET-related molecules, such as histones, has been shown in the glomerular lesions of AAV (10, 24, 25).…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, activated neutrophil infiltration in an inflammatory site is associated with some autoimmune disorders such as vasculitis. 44 It therefore appeared crucial to determine whether neutrophils are involved in cross-tolerance or cross-priming. Our observations that neutrophils cross-present antigens to naive T cells in vitro and that Ova-pulsed neutrophils induce naive OT1 CD8 ϩ T-cell proliferation in vivo were not sufficient to speculate about a role for neutrophils in cross-tolerance versus cross-priming.…”
Section: Discussionmentioning
confidence: 99%
“…This disease results in occasionally fatal sequelae such as the formation of aneurysms in the coronary arteries. Although the current standard treatment regimen consists of administration of large doses of globulin preparations, this approach is not always satisfactory (10,44). Murata et al conducted an analysis on children with Kawasaki disease and found that C. albicans extract (CADS) isolated from the stool specimens of the patients induced coronary angiitis in mice that resembled Kawasaki disease (8,24,25).…”
Section: Angiitis Induced By Caws and Predicted Mechanismmentioning
confidence: 99%